2022
DOI: 10.3390/biomedicines10112778
|View full text |Cite
|
Sign up to set email alerts
|

Fats, Friends or Foes: Investigating the Role of Short- and Medium-Chain Fatty Acids in Alzheimer’s Disease

Abstract: Characterising Alzheimer’s disease (AD) as a metabolic disorder of the brain is gaining acceptance based on the pathophysiological commonalities between AD and major metabolic disorders. Therefore, metabolic interventions have been explored as a strategy for brain energetic rescue. Amongst these, medium-chain fatty acid (MCFA) supplementations have been reported to rescue the energetic failure in brain cells as well as the cognitive decline in patients. Short-chain fatty acids (SCFA) have also been implicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 124 publications
(211 reference statements)
0
8
0
Order By: Relevance
“…Our functional analysis of the GM was prompted by research findings showing the ability of SCFAs to ameliorate certain AD hallmarks in mouse models [ 55 ], however our results, somewhat surprisingly, showed only reduced levels of anti-inflammatory propionic acid and a higher abundance of valeric acid in WT DSS mice compared to WT controls, while no differences were observed for Tg2576 DSS animals.…”
Section: Discussionmentioning
confidence: 67%
“…Our functional analysis of the GM was prompted by research findings showing the ability of SCFAs to ameliorate certain AD hallmarks in mouse models [ 55 ], however our results, somewhat surprisingly, showed only reduced levels of anti-inflammatory propionic acid and a higher abundance of valeric acid in WT DSS mice compared to WT controls, while no differences were observed for Tg2576 DSS animals.…”
Section: Discussionmentioning
confidence: 67%
“…Unlike longer chain fatty acids which require specific transporters such as CD36, fatty acid transport proteins (FATPs) and carnitine shuttle ( Heidt et al, 2023 ), medium chain fatty acid (MCFA) arising from MCT do not rely on specific transporters to pass through the mitochondrial membrane ( Miyagawa et al, 2018 ; Heidt et al, 2023 ). Through passive diffusion, MCFA can be easily and directly transported into the mitochondrial matrix ( Heidt et al, 2023 ), and enhances beta-oxidation (β-oxidation) rate in hepatocytes, which ultimately increases the serum KB concentration ( Ameen et al, 2022 ). In response to the increased levels of KBs, brain energy metabolism and cognitive functions are improved significantly ( Ameen et al, 2022 ).…”
Section: Ketogenic Dietmentioning
confidence: 99%
“…Through passive diffusion, MCFA can be easily and directly transported into the mitochondrial matrix ( Heidt et al, 2023 ), and enhances beta-oxidation (β-oxidation) rate in hepatocytes, which ultimately increases the serum KB concentration ( Ameen et al, 2022 ). In response to the increased levels of KBs, brain energy metabolism and cognitive functions are improved significantly ( Ameen et al, 2022 ). Increased levels of KB and brain energy might be important especially for the treatment of patients with AD, impaired brain energy metabolism and cognitive dysfunction ( Krikorian et al, 2012 ).…”
Section: Ketogenic Dietmentioning
confidence: 99%
“…One potential approach involves the use of medium-chain triglycerides, or medium-chain fatty acids, which are usually defined as fatty acids with a chain length of six to ten or twelve carbon atoms. These include caproic acid (C6), caprylic acid (C8), capric acid (C10), and, under certain circumstances, lauric acid (C12) [ 16 , 17 ]. The background to their therapeutic application is based on findings of considerable impairments in glucose metabolism in the brains of patients with dementia [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…This connection is also known as the astrocyte-neuron lactate shuttle (ANLS) [ 24 ]. Furthermore, research has identified other indirect ways, in which MCFAs may beneficially modulate energy metabolism in the brain, for example, by positively affecting aspects of dementia-related mitochondrial dysfunction [ 16 ]. Cell lines from AD mouse models incubated with C10 showed significant positive effects on the mitochondrial respiratory chain, enzyme activity, and an overall increase in mitochondrial number.…”
Section: Introductionmentioning
confidence: 99%